Effect of dispersion methods on the performance of novel rigid copolymer polyurethane nanocomposites based on graphene nanofillers. Issue 4 (4th March 2022) - Albozahid, Muayad; Naji, Haneen Zuhair; Alobad, Zoalfokkar Kareem; Saiani, Alberto
ABSTRACT: The Rigid Copolymer Polyurethanes (RCPUs) as nanocomposites were synthesized by in-situ polymerization (ISP), melt compounding (MC), and solution mixing (SM) with wide range of weight ratios of graphite nanoplatelets (GNP). The blending process was utilized to obtain well- dispersed of GNP and thus strong interaction, leading to an effective performance of the RCPU/GNP nanocomposites. The structure of RCPU/GNP nanocomposites was studied using FTIR test. The thermal stability of RCPU nanocomposites was seen by TGA analysis, showing an increase with addition of GNP nanofillers. Rheology analysis revealed network formation with well-dispersed GNP regarding different dispersion approaches. Thermal and electrical tests were also conducted, approving that dispersion and interaction of GNP can play a crucial role for enhancing the thermal and electrical properties. Such a significant improvement in RCPU matrix performance could lead to the use of this material for different application. Graphical abstract: uf0001